The tribe Rhaconotini (Hymenoptera: Braconidae: Doryctinae) of South Korea, with description of a new Rhaconotus Ruthe species - Belokobylskij, Sergey A.; Ku, Deok-Seo; Broad, Gavin R. (Zootaxa, 2021)
The genera and species of the tribe Rhaconotini are reviewed for the fauna of the Korean Peninsula. A new Rhaconotus species, Rh. koreanus sp. nov., is described and illustrated. The generic placement of the Oriental Rhyssalus striatulus Cameron is corrected and Ipodoryctes species described from China, overlooked in a recent publication on Rhaconotini, are reclassified. The following are new combinations: Rhyssalus striatulus Cameron, 1909 = Mimipodoryctes striatulus (Cameron, 1909) comb. nov.; Ipodoryctes guizhouensis Tang et Chen, 2011 = Rhaconotinus (Rhaconotinus) guizhouensis (Tang et Chen, 2011), comb. nov.; Ipodoryctes hebeiensis Tang et Chen, 2011 = Rhaconotinus (Rhaconotinus) hebeiensis (Tang et Chen, 2011), comb. nov.; Ipodoryctes rugosus Tang et Chen, 2011 = Rhaconotinus (Rhaconotinus) rugosus (Tang et Chen, 2011), comb. nov.; Ipodoryctes rutilans Tang et Chen, 2011 = Rhaconotinus (Rhaconotinus) rutilans (Tang et Chen, 2011), comb. nov.; Ipodoryctes wuyiensis Tang et Chen, 2011 = Rhaconotinus (Rhaconotinus) wuyiensis (Tang et Chen, 2011), comb. nov.; and Ipodoryctes liui Tang et Chen, 2011 = Rhaconotinus (Hexarhaconotinus) liui (Tang et Chen, 2011), comb. nov.